A First Plasmodium vivax Natural Infection Induces Increased Activity of the Interferon Gamma-Driven Tryptophan Catabolism Pathway - Santos, Rafaella Oliveira dos; Cruz, Maria Geuziane Soares da; Lopes, Stefanie Costa Pinto; Oliveira, Lucas Barbosa; Nogueira, Paulo Afonso; Lima, Emerson Silva; Soares, Irene Silva; Kano, Flora Satiko; Carvalho, Andréa Teixeira de; Costa, Fabio Trindade Maranhão; Ganoza, Christian A.; Lacerda, Marcus Vinicius Guimarães de; et al. (Frontiers in Microbiology, 2020)
The human immune response that controls Plasmodium infection in the liver and blood stages of the parasite life cycle is composed by both pro- and anti-inflammatory programs. Pro-inflammatory responses primarily mediated by IFN-γ controls the infection, but also induce tolerogenic mechanisms to limit host damage, including the tryptophan (TRP) catabolism pathway mediated by the enzyme Indoleamine 2,3-Dioxygenase (IDO1), an enzyme that catalyses the degradation of TRP to kynurenines (KYN). Here we assessed total serum kynurenines and cytokine dynamics in a cohort of natural Plasmodium vivax human infection and compared them to those of endemic healthy controls and other febrile diseases. In acute malaria, the absolute free kynurenine (KYN) serum levels and the KYN to TRP (KYN/TRP) ratio were significantly elevated in patients compared to healthy controls. Individuals with a diagnosis of a first malaria episode had higher serum KYN levels than individuals with a previous malaria episode. We observed an inverse relationship between the serum levels of IFN-γ and IL-10 in patients with a first malaria episode compared to those of subjects with previous history of malaria. Kynurenine elevation was positively correlated with serum IFN-γ levels in acute infection, whereas, it was negatively correlated with parasite load and P. vivax LDH levels. Overall, the differences observed between infected individuals depended on the number of Plasmodium infections. The decrease in the KYN/TRP ratio in malaria-experienced subjects coincided with the onset of anti-P. vivax IgG. These results suggest that P. vivax infection induces a strong anti-inflammatory program in individuals with first time malaria, which fades with ensuing protective immunity after subsequent episodes. Understanding the tolerance mechanisms involved in the initial exposure would help in defining the balance between protective and pathogenic immune responses necessary to control infection and to improve vaccination strategies.